ASSESSING PRESIDENT SAMIA SULUHU HASSAN’S LEADERSHIP IMPACT ON TANZANIA’S SOCIO-ECONOMIC DEVELOPMENT: AN ANALYSIS OF STRATEGIC INITIATIVES AND POLICY OUTCOMES - Magasi, Chacha (Journal of Social Political Sciences, 2024)
The purpose of this study is to provide a rigorous evaluation of President Samia Suluhu Hassan’s leadership, focusing on its broader impact on Tanzania’s socio-economic development. As the first female president of Tanzania, her administration marks a critical juncture in the nation’s history, facing both significant challenges and opportunities for transformative change. This research examines her strategic efforts in economic recovery, infrastructure development, and the management of the COVID-19 pandemic, assessing how these policies have influenced public health outcomes, economic growth, and governance. Additionally, the study explores her initiatives to advance gender equality, particularly addressing the persistent disparities in both urban and rural areas. A mixed-methods approach was employed, combining quantitative data on economic performance, public health metrics, and gender representation with qualitative insights gathered from focus group discussions involving policymakers, analysts, and experts. The findings reveal notable progress under President Hassan’s leadership in areas such as economic recovery, gender equality, and infrastructure development, particularly through projects like the Standard Gauge Railway (SGR) and the Julius Nyerere Hydropower Station. However, challenges such as financial constraints and project delays remain. The study’s novelty lies in its comprehensive analysis of President Hassan’s multifaceted policy impacts, contributing new knowledge to the discourse on governance, sustainable development, and gender equality. Key implications include recommendations for enhanced infrastructure investment, improved pandemic preparedness, and targeted support for small and medium-sized enterprises (SMEs).